Pengaruh Bisnis Analitik dan Bisnis Intelijen terhadap Optimasi Operasional Sehingga Meningkatkan Kinerja Keuangan Distributor Alat Kesehatan di Indonesia - Agus Neny (AKUNTANSI 45, 2024)
The purpose of this study is to prove how business analytics (BA) and business intelligence (BI) implementation affects Indonesian medical equipment distributors' financial performance and operational optimization. Sixty representatives of medical equipment distribution enterprises with transaction values over one billion rupiah participated in an online questioner that was used to collect data. The analysis's findings show that these organizations' financial performance is significantly and favourably impacted by the application of business analytics, operational optimization, and intelligence. Businesses may improve competitiveness, streamline operations, and make better decisions by implementing business analytics and intelligence. Furthermore, the financial performance is greatly enhanced by the operational optimization that comes from the application of BI and BA. The created study model incorporates Information Processing Theory (IPT) and shows how corporate management practices are impacted by the success of BI implementation, which in turn influences organizational process effectiveness. Performance planning and measurement are directly impacted by BA techniques as well. This study has significant ramifications for business professionals that use business analytics and intelligence as strategic instruments to improve their organizations' financial performance, especially in the medical equipment sector. According to the results, businesses who use BI and BA may optimize their processes more successfully, which improves their financial performance. In summary, this study emphasizes how crucial it is to include BI and BA technology into business operations and strategic decision-making.